KHARKIV CYCLING INFRASTRUCTURE DEVELOPMENT FEATURES - Sokolenko, Anna (Human Geography Journal, 2015)
The article focuses on cycling infrastructure development features in a number of European cities. The article outlines the main problems of a big city’s transport infrastructure and points out the advantages of a network of cycle paths and bike racks <a title="Показать примеры употребления" href="http://www.lingvo.ua/ru/Search/Translate/GlossaryItemExtraInfo?text=%d0%b2%d0%bd%d0%b5%d0%b4%d1%80%d0%b5%d0%bd%d0%b8%d0%b5&translation=introduction&srcLang=ru&destLang=en">introduction to an urban space. Approach, based on the relevant researches analysis and successful experience of some western countries, <a title="Показать примеры употребления" href="http://www.lingvo.ua/ru/Search/Translate/GlossaryItemExtraInfo?text=%d0%be%d0%b1%d0%be%d1%81%d0%bd%d0%be%d0%b2%d1%8b%d0%b2%d0%b0%d1%82%d1%8c&translation=substantiate&srcLang=ru&destLang=en">substantiates creation of a full-fledged bicycle infrastructure in Kharkiv. By means of Delfi questionnaire citizent’s opinion concerning the question of creation and use of bicycle infrastructure is revealed; potential target audience is defined.